Multifilament electrospun scaffolds for soft tissue reconstruction - Abhari, R; Carr, A; Mouthuy, P (Elsevier, 2018)
While the development of electrospun filaments has remained limited to date, their emergence opens the possibility of creating advanced multifilament scaffolds. Multifilament scaffolds can be designed with sufficient mechanical properties to be used for soft tissue engineering, while still retaining high porosity to encourage cell-mediated repair. This chapter focuses on manufacturing methods for electrospun filaments and postprocessing techniques to improve material properties. The use of textile techniques, such as twisting, braiding, and weaving, in assembling filaments into multifilament yarns is discussed. Finally, electrospun yarns used as multifilament scaffolds for soft tissue repair are explored, with an emphasis on patches and sutures for the anterior cruciate ligament and the rotator cuff. Although most developments have been limited to handmade multifilament yarns, the introduction of semiindustrialized methods for filament electrospinning will likely facilitate translation of multifilament electrospun scaffolds into clinics in the near future.